Clinical Characteristics of Herpes Simplex Virus Urethritis Compared With Chlamydial Urethritis Among Men. Issue 2 (February 2017) - Ong, Jason J.; Morton, Anna N.; Henzell, Helen R.; Berzins, Karen; Druce, Julian; Fairley, Christopher K.; Bradshaw, Catriona S.; Read, Tim RH; Hocking, Jane S.; Chen, Marcus Y.
Abstract : Background: The aim of this study was to ascertain the clinical characteristics associated with herpes simplex virus (HSV) urethritis in men and to compare those with chlamydial urethritis. Methods: We compared clinical and laboratory data from men diagnosed with polymerase chain reaction confirmed HSV urethritis with those of men with chlamydial urethritis presenting to Melbourne Sexual Health Centre between 2000 and 2015. Results: Eighty HSV urethritis cases were identified: 55 (68%, 95% confidence interval, 58–78) were by HSV-1 and 25 (32%, 95% confidence interval, 22–42) by HSV-2. Compared with chlamydial urethritis, men with HSV urethritis were significantly more likely to report severe dysuria (20% vs 0%, P < 0.01) or constitutional symptoms (15% vs 0%, P < 0.01). Men with HSV urethritis were significantly more likely to have meatitis (62% vs 23%, P < 0.01), genital ulceration (37% vs 0%, P < 0.01), or inguinal lymphadenopathy (30% vs 0%, P < 0.01) but less likely to have urethral discharge (32% vs 69%, P < 0.01). There was no significant difference in the proportion of men who had raised (≥5) polymorphonuclear leukocytes per high-powered field between the two groups ( P = 0.46). Conclusions: The clinical presentation of HSV urethritis in men may differ from those of chlamydial urethritis and guide testing for HSV in men presenting with non-gonococcal urethritis. Abstract : Herpes simplex virus urethritis can be associated with distinctive features not usually associated with chlamydial urethritis: severe dysuria, constitutional symptoms, meatitis, genital ulceration, and lymphadenopathy. When present clinicians should consider herpes simplex virus testing.